2010
DOI: 10.1002/jcp.22180
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine induces matrix metalloproteinase‐2 (MMP‐2) and MMP‐9 down‐regulation in human leukemia U937 cells via Ca2+/ROS‐mediated suppression of ERK/c‐fos pathway and activation of p38 MAPK/c‐jun pathway

Abstract: Caffeine attenuated invasion of human leukemia U937 cells with characteristic of decreased protein expression and mRNA levels of matrix metalloproteinase-2 (MMP-2) and MMP-9. Down-regulation of MMP-2 and MMP-9 in U937 cells was abrogated by abolishment of caffeine-elicited increase in intracellular Ca(2+) concentration and ROS generation. Pretreatment with BAPTA-AM (Ca(2+) chelator) and N-acetylcysteine (ROS scavenger) abolished caffeine-induced ERK inactivation and p38 MPAK activation. Moreover, caffeine trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…MMP-2 and MMP-9 are important members of the MMP family, which and promote cancer-cell migration and invasion by degrading extracellular matrix components (2,(14)(15)(16)(17)). An increasing number of studies demonstrated that MMP-2 and MMP-9 have important roles in GBM angiogenesis and can be regulated by multiple pathways (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-2 and MMP-9 are important members of the MMP family, which and promote cancer-cell migration and invasion by degrading extracellular matrix components (2,(14)(15)(16)(17)). An increasing number of studies demonstrated that MMP-2 and MMP-9 have important roles in GBM angiogenesis and can be regulated by multiple pathways (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MMP-2 and MMP-9 are mostly associated with migration and invasion in multiple tumor types (14)(15)(16). Further studies have shown that the expression of MMP-2 and MMP-9 in several cancer types is mediated by numerous signaling pathways, which include the hedgehog signaling pathway, the wnt/β-catenin pathway, the phosphoinositide-3 kinase (PI3K)/AKT pathway and the mitogen-activated protein kinase (MAPK) pathway (10,17,18). It has been suggested that the hedgehog signaling pathway is cross-linked with other signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Although caffeine has been reported to reduce cell migration and invasion, the mechanism responsible for these effects remains unclear [7,17]. Caffeine alters IP3R and subsequently, intracellular calcium levels, which reduce migration and invasion in human glioma cells [7].…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine alters IP3R and subsequently, intracellular calcium levels, which reduce migration and invasion in human glioma cells [7]. In non-glioma cells, caffeine decreases invasion of human leukemia U937 cells through the Ca 2+ /ROS-mediated suppression of ERK/c-fos and activation of p38 MAPK/ c-jun pathways [17]. Furthermore, caffeine inhibits the motility of extra-villous trophoblasts by blocking the mammalian target of rapamycin complex 2 and Akt [18].…”
Section: Discussionmentioning
confidence: 99%
“…glaucocalyx (Lamiaceae) [288] Guggulsterone Triterpenoid Commiphora mukul (Burseraceae) [289,290] Gypenosides Triterpenoid Gynostemma pentaphyllum (Cucurbitaceae) [291,292] Helenalin Sesquiterpenoid Arnica spp. (Asteraceae) [293] Linalool Monoterpenoid Coriandrum sativum (Apiaceae), widespread [294] ( [345][346][347] Camptothecin Quinoline Camptotheca acuminata (Nyssaceae) [7,348] Cepharanthine Isoquinoline Stephania cepharantha (Menispermaceae) [349,350] ( vate, which is an efficient scavenger of H 2 O 2 [75][76][77][78]. Second, glucose metabolism through the pentose phosphate pathway regenerates NADPH from NADP + in a reaction in which glucose-6-phosphate is converted into 6-phosphogluconolactone by the enzyme glucose-6-phosphate dehydrogenase.…”
Section: Pro-oxidant Natural Products With Anticancer Activitymentioning
confidence: 99%